Lateral channel migration rates for the Rio Bermejo - Repasch, Marisa N; Scheingross, Joel S; Cook, Kristen L; Sachse, Dirk; Dosch, Sophia; Orfeo, Oscar (In: Repasch, MN et al. (2023): River water chemistry, channel morphometrics, and river incision data for the Rio Bermejo, Argentina [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.959938, 2023)
To measure lateral migration rates, we mapped the active channel from Landsat imagery for four different years, yielding three time-intervals (1988-1993, 1993-2002, and 2002-2015). For each interval, we compared the locations of the two channel centerlines. Between successive crossing points of the two centerlines, we measured the area between the two lines, which represents the area traversed by the channel centerline over the given timespan. This area, divided by the along-channel distance and the timespan between images, yields a lateral migration rate for that channel segment. We averaged these rates over 15 km long channel segments. This length scale was chosen so that, along the meandering reach of the river, at least three individual meander bends are comprised in a single channel migration value.
Keywords: Argentina; channel migration rates; fluvial geomorphology; Foreland basin; river morphometrics; water chemistry